Indoor air quality in urban residential: Current status, regulation and future research for Indonesia - Ezra Ganesha Prihardanu; Haryoto Kusnoputranto; Herdis Herdiansyah (International Journal of Public Health Science (IJPHS), 2021)
Modern society spends more time indoors, which has led to the hypothesis that indoor exposure can better represent the effects of air pollution at the individual level. Studies on the landscape of urban residential indoor air quality have never been carried out nationally in Indonesia. After 70 years of commitment to standardize the health aspects of the home in Indonesia, this study intends to make a chronological reflection on the Indonesian government's policy in residential indoor air quality. This study raised and analyzed several questions in the national and local context from the previous research. The government's various policies and regulations are chronologically listed to see the development and look for regulatory or implementation gaps. The indicators of insufficient ventilation and indoor air quality in much Indonesian urban housing have been shown in previous studies, encouraging this study to be necessary. This study used a chronological review using national and international journals. Previous studies have shown possibilities to estimate the landscape of indoor pollution exposure effectively using a socio-economic approach as a part. The latest national housing survey results can be used as references to discover the housing landscape status in Indonesia for further research suggestions.